Reciprocal interactions between mitral valve endothelial and interstitial cells reduce endothelial-to-mesenchymal transition and myofibroblastic activation. (March 2015) - Shapero, Kayle; Wylie-Sears, Jill; Levine, Robert A.; Mayer, John E.; Bischoff, Joyce
Abstract: Thickening of mitral leaflets, endothelial-to-mesenchymal transition (EndMT), and activated myofibroblast-like interstitial cells have been observed in ischemic mitral valve regurgitation. We set out to determine if interactions between mitral valve endothelial cells (VECs) and interstitial cells (VICs) might affect these alterations. We used in vitro co-culture in Transwell™ inserts to test the hypothesis that VICs secrete factors that inhibit EndMT and conversely, that VECs secrete factors that mitigate the activation of VICs to a myofibroblast-like, activated phenotype. Primary cultures and clonal populations of ovine mitral VICs and VECs were used. Western blot, quantitative reverse transcriptase PCR (qPCR) and functional assays were used to assess changes in cell phenotype and behavior. VICs or conditioned media from VICs inhibited transforming growth factor β (TGFβ)-induced EndMT in VECs, as indicated by reduced expression of EndMT markers α-smooth muscle actin (α-SMA), Slug, Snai1 and MMP-2 and maintained the ability of VECs to mediate leukocyte adhesion, an important endothelial function. VECs or conditioned media from VECs reversed the spontaneous cell culture-induced change in VICs to an activated phenotype, as indicated by reduced expression of α-SMA and type I collagen, increased expression chondromodulin-1 (Chm1), and reduced contractile activity. These results demonstrate that mitral VECs and VICs secrete soluble factors that can reduce VIC activation and inhibit TGFβ-driven EndMT, respectively. These findings suggest that the endothelium of the mitral valve is critical for the maintenance of a quiescent VIC phenotype and that, in turn, VICs prevent EndMT. We speculate that the disturbance of the ongoing reciprocal interactions between VECs and VICs in vivo may contribute to the thickened and fibrotic leaflets observed in ischemic mitral regurgitation, and in other types of valve disease. Graphical abstract: Highlights: Quiescent valve endothelial and interstitial cell phenotypes were approximated in vitro . Valve interstitial cells inhibited TGFβ-induced endothelial to mesenchymal transition. Valve endothelial cells reversed the myofibroblastic phenotype of interstitial cells.